Chinese Herbal Medicine Xingnaojing Injection for Acute Ischemic Stroke: An Overview of Systematic Reviews and Meta-Analyses - Zi-Yu Tian; Zi-Yu Tian; Zi-Yu Tian; Lu-Da Feng; Lu-Da Feng; Yao Xie; De-Hao Xu; Chong-Yang Zhang; Ling-Bo Kong; Ling-Bo Kong; Rong-Rong An; Li-Fang Ma; et al. (Frontiers Media S.A., 2021)
Background: Xingnaojing injection (XNJ) is the only Chinese herbal injection approved for both intracerebral hemorrhage and ischemic stroke (IS) first-aid on ambulances in China; many systematic reviews (SRs) and meta-analyses (MAs) of XNJ on stroke have been published. The purpose of this research was to evaluate and summarize the current evidence on XNJ for IS.Methods: A comprehensive search was conducted for SRs and MAs of XNJ on IS in seven databases up to January 1, 2021. Two authors independently identified SRs and MAs, extracted data, assessed the quality of the included SRs and MAs using the Assessment of Multiple Systematic Reviews 2 (AMSTAR 2), and assessed quality of evidence using the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE).Results: A total of 10 SRs met the inclusion criteria. The quality of included SRs using AMSTAR 2 was critically low as the critical items were poorly reported. Only 10% of SRs reported 50% of the 16 items, while the remaining 90% SRs reported just less than half of the items on AMSTAR 2. For GRADE, 7 (35%) of outcomes had low-quality evidence, 10 (50%) with very low, and 3 (15%) with moderate quality evidence. Very low to low quality of evidence indicated XNJ plus conventional therapy (CT) alleviated the neurological deficits of acute IS. Moderate-quality evidence showed XNJ plus CT reduced mortality when compared to Danshen injection plus CT, and very low-quality evidence showed XNJ plus CT could not improve the degree of coma, while low-quality evidence indicated the opposite. Mild adverse events in the CT group were less than those in the XNJ plus CT group, and there were no serious adverse events, but there was no statistical difference between the two groups. The included 10 SRs indicated that XNJ was used for acute IS, but only four SRs (40%) reported the course of disease.Conclusion: XNJ appears to be effective and safe for acute IS in improving the neurological deficits, but the evidence is not robust enough. However, whether administering XNJ immediately after or within 24 h of IS is best remains unknown due to the lack of data. Well-designed large-scale randomized controlled trials with measurable outcomes are required in future studies.